AM1241 inhibits chondrocyte inflammation and ECM degradation through the Nrf2/HO-1 and NF-κB pathways and alleviates osteoarthritis in mice - Zhuan Zou; Songmu Pan; Changzheng Sun; Jiyong Wei; Yi Xu; Kaizhen Xiao; Jinmin Zhao; Ronghe Gu (Molecular Medicine)
Abstract Background This study aimed to investigate the impact of AM1241 on lipopolysaccharide (LPS)-induced chondrocyte inflammation in mice and its potential mechanism for improving osteoarthritis (OA). Methods The OA mice model was established employing the refined Hulth method. The impact of different concentrations of AM1241 on mice chondrocyte activity was detected using CCK-8. Changes in the levels of LPS-induced inflammatory factors and cartilage extracellular matrix (ECM) degradation in chondrocytes were determined by western blot, RT-qPCR, ELISA, and immunofluorescence assays, respectively. The specific action modes and binding sites of AM1241 with NEMO/IκB kinases (IKKs) in the NF-κB pathway and Keap1 protein in the Nrf2 pathway were predicted via molecular docking and molecular dynamics simulation, and the NF-κB and Nrf2 pathways were detected using western blot and immunofluorescence. In vivo, the impact of AM1241 on OA mice was analyzed through safranin-fast green staining, IHC staining, Mankin score, and microCT. Results AM1241 inhibited the levels of LPS-induced transforming growth factor-β (TGF-β1), tumor necrosis factor-α (TNF-α), interleukin 6 (IL-6), matrix metalloproteinase-13 (MMP-13), and a disintegrin and metalloproteinase with thrombospondin motif 5 (ADAMTS-5) and diminished the degradation of type II collagen and Aggrecan. For the mechanism, AM1241 regulated the NF-kB and Nrf2/HO-1 signaling pathways by binding to NEMO/IKKβ and Keap1 target proteins and suppressed the activation of the NF-κB signaling pathway by activating the Nrf2 in chondrocytes. In vivo, AM1241 inhibited bone anabolism, mitigated articular cartilage hyperplasia and wear, and reduced the Mankin score in mice, thereby hindering the development of OA. Conclusion AM1241 inhibited activation of the NF-κB signaling pathway via activating Nrf2. It suppressed the expression of inflammation factors and the degradation of ECM in vitro, and improved OA in mice in vivo, suggesting its potential as an effective drug candidate for the treatment of OA. The remarkable efficacy of AM1241 in alleviating murine OA positions it as a potential therapeutic strategy in the clinical management of OA diseases.